HISTOLOGICAL AND IMMUNOHISTOCHEMICAL STUDY OF NASAL POLYPS - YOSHIMI, RYUICHIRO; TAKASAKI, KENJI; TSURUMOTO, HIYOSHI; KOBAYASHI, TOSHIMITSU; KANDA, YUKIHIKO; TAKAMURA, HIROMITSU (Nippon Jibi Inkoka Gakkai Kaiho, 1996)
Nasal polyps, in general, have been histologically classified as edematous, adenocystic and fibrous types. It has recently been pointed out that eosinophilic infiltration in nasal polyps has increased along with an increase in nasal allergy. The purpose of this study was to classify the nasal polyps histologically and to examine the mode of infiltration and activation of eosinophils by means of immunohistochemistry. The subjects were 101 patients who underwent surgery for nasal polyps. There were 66 males and 35 females ranging in age from 12 to 76 years. Resected polyps were fixed in formalin, embedded in paraffin, and sliced at a thickness of 4μm. Hematoxylin-eosin staining and streptavidin-biotinyl peroxidase complex staining were used to detect eosinophils. The results were as follows: 1) The nasal polyps were, histologically, edematous in 88.1%, adenocystic in 47.5%, and fibrous in 19.8%. 2) The number and distribution of EGl-positive cells and EG2-positive cells were almost the same in the superficial layer of the lamina propria. This study suggests that eosinophilic infiltration into nasal polyps occurs mainly in edematous polyps and that the majority of the infiltrating eosinophils are activated.